2017
DOI: 10.1080/00016489.2017.1366052
|View full text |Cite
|
Sign up to set email alerts
|

Relative frequencies of symptoms and risk factors among patients with chronic rhinosinusitis with nasal polyps using a case-control study

Abstract: By comparing symptoms and risk factors of patients with CRSwNP with those of a large population-based control group and testing them in a multiple logistic regression model, we have been able to generate data that address key research interests in CRSwNP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…The incidence (but not the gender proportion) of smokers (32.6%) follows that of the Portuguese population 41 . In a manner similar to our patients, other studies have also reported a higher prevalence of smokers in sinusitis groups 42 , as well as a lower proportion of NP patients who smoke, both in national and international cohorts 40,43,44 . Although Lund-Mackay scores aren't used in clinical decision, they represent the extent of sinus inflammation (even though the score may be different from 0 in any given healthy individual).…”
Section: Discussionsupporting
confidence: 91%
“…The incidence (but not the gender proportion) of smokers (32.6%) follows that of the Portuguese population 41 . In a manner similar to our patients, other studies have also reported a higher prevalence of smokers in sinusitis groups 42 , as well as a lower proportion of NP patients who smoke, both in national and international cohorts 40,43,44 . Although Lund-Mackay scores aren't used in clinical decision, they represent the extent of sinus inflammation (even though the score may be different from 0 in any given healthy individual).…”
Section: Discussionsupporting
confidence: 91%
“…[16][17][18] Recent studies have also identified the importance of nasal congestion or obstruction, nasal drip, and loss of smell in patients with CRS with nasal polyps. 23,24 Building on the identification of symptoms as relevant to the population with nasal polyps, participants in the current study discussed their symptoms in terms of frequency, duration, and severity, providing an in-depth understanding of the symptomatology, the specific characteristics of which were not detailed within the current published literature. [16][17][18] Relationships identified between different nasal polyps symptoms during the concept elicitation interviews demonstrated the complexity of the patient experience in this condition, with links between the primary symptom of nasal congestion and symptoms occurring as a consequence of the primary symptoms (eg, difficulty breathing through the nose, cough, loss of smell, and loss of taste).…”
Section: Discussionmentioning
confidence: 99%
“…Nasal congestion was reported in 95-100% of patients with CRSwNP in North America 17,27 , 73-88% of patients in Europe 34,35 , and 76-81% of patients in Asia 31,36 . Loss of smell was reported for 56-84% of patients with CRSwNP in North America 16,27 , 35-90% of patients in Europe 28,34,35,37,38 , and 30-100% of patients in Asia [30][31][32]36,39 . Sneezing was reported for 88% of patients in North America 26 , 12-73% of patients in Europe 28,34,35,38 , and 27-51% of patients in Asia 31,33 .…”
Section: Symptomsmentioning
confidence: 99%
“…Loss of smell was reported for 56-84% of patients with CRSwNP in North America 16,27 , 35-90% of patients in Europe 28,34,35,37,38 , and 30-100% of patients in Asia [30][31][32]36,39 . Sneezing was reported for 88% of patients in North America 26 , 12-73% of patients in Europe 28,34,35,38 , and 27-51% of patients in Asia 31,33 . Headache was reported for 33-95.8% of patients in North America 27,40 , 20-41% of patients in Europe 33,34 , and 2-76% of patients in Asia 33,36 .…”
Section: Symptomsmentioning
confidence: 99%
See 1 more Smart Citation